2023
DOI: 10.1587/elex.20.20230386
|View full text |Cite
|
Sign up to set email alerts
|

4-channel, 224Gb/s PAM-4 optical transmitter with group delay compensation in 130-nm BiCMOS technology

Wentian Fan,
Yingmei Chen,
Jiquan Li
et al.

Abstract: A compact 4-channel 224 Gb/s PAM4 optical transmitter in 130nm SiGe BiCMOS technology is presented employing 3-tap feedforward equalizer (FFE) and continuous time linear equalizer (CLTE) techniques. One pre-emphasis tap and CLTE structures broadened the bandwidth to 26 GHz. Moreover, the peak-peak value of group delay for this system is reduced to 6.7 ps by adopting one pre-fall tap structure. The output stage employs current mode logic circuits to achieve high modulation currents. This chip occupies an area o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15]. However, the reduced symbol levels render the PAM-4 scheme less tolerant to the residual inter-symbol interference and amplitude noise [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The data-traffic explosion driven by cloud computing, 5G networks, industrial IoT, and virtual reality has accelerated the demand for high-speed SerDes transceivers to provide massive data throughput [1,2,3,4,5,6,7,8]. Previous studies have demonstrated that four-level pulse amplitude modulation (PAM-4) is superior to non-return-to-zero (NRZ) for the 56∼112-Gb/s serial data communications due to its doubled spectral efficiency, halved Nyquist frequency, and relaxed clock speeds [9,10,11,12,13,14,15]. However, the reduced symbol levels render the PAM-4 scheme less tolerant to the residual inter-symbol interference and amplitude noise [16,17].…”
Section: Introductionmentioning
confidence: 99%